Exercise Motivations: Differentiation of International and Domestic College Students - Cho, Dongwook; Beck, Steve; Kim, Sung Kyeom (Journal of International Students, 2020)
As the number of international and domestic college students has increased, the importance of developing healthy lifestyles has been getting significant attention from college administrators. The current study was designed to determine if differences occur in exercise motivation between international and domestic college students. A total of 155 college students from a southwestern U.S. university completed the Exercise Motivations Inventory–2 through the university’s online active research system. Analyses indicated that international students possessed a higher motivation to exercise for revitalization, while domestic students were more motivated for a challenge, competition, and social recognition. The findings suggest that campus health professionals or wellness administrators may need to utilize different strategies to promote the health of international college students through exercise programs.